Repeated walking challenge campaign participation increases step averages among Mexican Americans living in an inactive U.S.-Mexico border community - Roy Valenzuela; Mary Miller; Jennifer J. Salinas (Springer, 2023)
Abstract Mexican Americans are among the least active race/ethnic groups in the United States, most notably during leisure time. We sought to ascertain the effect of repeated participation in community-based walking challenges on average steps as a potential strategy for improving physical activity engagement in a predominately Hispanic community in far west Texas. A total of 354 participants were recruited through a community-wide walking challenge campaign. Data were analyzed at baseline and 2 weeks post-challenge participation. We used step tracker data to determine quantifiable differences by previous challenge participation. Repeated challenge participation was associated with greater baseline step averages; however, there was no dose effect for the number of previous challenges. One previous challenge participation was no different from multiple challenges. Additionally, the type of challenge increased the likelihood of repeated challenge participation. Findings from this study provide evidence that regular community-level walking challenge campaigns contribute to sustained walking among Mexican Americans at the community level.